Фармакологическая модуляция HSP70-зависимых механизмов эндогенной нейропротекции в условиях пренатальной хронической алкоголизации цереброкурином и тиоцетамом - Соколик, Е. П.; Стеценко, В. А.; Стеценко, Володимир Олександрович; Соколик, Олена Петрівна; Sokolik, E. P.; Stetsenko, V. A. (Олимп, 2015)
Данными исследованиями показано, что применение Цереброкурина и Тиоцетама по предложенной нами схеме оказывает позитивное воздействие на экспрессию HSP и HIF и значительно повышает их концетрацию в головном мозге в условиях пренеатальной алкого-лизации. Полученные нами результаты исследования раскрывают не только молекулярный механизм нейропротективного действия Цереброкурина и Тиоцетама, но и являются экспериментальным обоснованием для внедрения их в клиническую практику. One of the primary reactions of the genome in response to stress is different genesis induction of heat shock proteins – HSP (Heat shock proteins). The purpose of this study was to investigate the concentration of heat shock protein (HSP70) and hypoxia-inducible factor (HIF- 1) in the brain of rats undergoing chronic prenatal alcoholism in different periods of ischemia and define the role of these proteins in the implementation of neuroprotective effect of Cerebrocurin and Tiocetam. Cerebrocurin and Tiocetam directly or indirectly can modulate the expression of early response genes c-fos and thus the «run» software adaptation protein synthesis (including HSP and HIF) in neurons with acute cerebral ischemia. These studies have shown that using Cerebrocurin and Tiocetam on our proposed scheme has a positive impact on the expression of HSP and HIF and significantly increases their effect on concentration in the brain under conditions of prenatal alcoholism. Thus, our results reveal not only the study of the molecular mechanism of neuroprotective activity of Cerebrocurin and Tiocetam, but are experimental basis for their introduction into clinical practice.
Pharmacological modulation of HSP70 – dependent mechanisms of endogenous neuroprotection in conditions of prenatal chronic alcoholism by Cerebrocurin and Tiocetam